Selectivity of an Active Natural Zeolite in Catalytic Conversion Process of Bangkirai, Kruing and Kamper Woods Biofuel to Gasoline Fraction - Wega Trisunaryanti (Universitas Gadjah Mada, 2001)
The selectivity of an active natural zeolite (ZAAH) in catalytic conversion process of Bangkirai, Kruing and Kamper woods biofuels has been studied. The ZAAH catalyst was prepared from a natural zeolite (ZA) treated with acids solution (1% HF and 6M HCI) and hydrothermal then calcined at 500 °C and oxidized at 400 °C under nitrogen and oxygen gas stream, respectively. Characterizations of the catalysts including Si/Al ratio and acidity were determined by atomic adsorption spectroscopy (AAS) and ammonia gas adsorption method, respectively. The conversion process was carried out in a flow reactor system at 400 °C, under N2 stream (20 mL/min). The biofuel was vaporized from the pyrolysis zone to the catalytic reactor. A liquid product was covered and analyzed by gas chromatograph (GC) and that connected with mass spectroscopy (GC-MS). The characterization results showed that the Si/AI ratio and acidity of the ZAAH were higher than that of the ZA catalyst. The GC-MS data showed that the highest product selectivity was 2,4-dimethyl heptane and 1,2-dimethyl benzene. The total product selectivity using the ZAAH catalyst (bangkirai = 68.10%; kruing = 54.76%; kamper = 50.72%) was higher than that of the ZA catalyst (bangkirai = 39.24%; kruing = 44.38%; kamper = 46.11%).